Angiogenin ameliorates corneal opacity and neovascularization via regulating immune response in corneal fibroblasts. Issue 1 (December 2016) - Lee, Seung; Kim, Kyoung; Joo, Kwangsic; Kim, Jae
Abstract Background Angiogenin (ANG), a component of tears, is involved in the innate immune system and is related with inflammatory disease. We investigated whether ANG has an immune modulatory function in human corneal fibroblasts (HCFs). Methods HCFs were cultured from excised corneal tissues. The gene or protein expression levels of interleukin (IL)-1beta (β), IL-4, IL-6, IL-8, IL-10, complements, toll-like receptor (TLR)4, myeloid differentiation primary response gene (MYD)88, TANK-binding kinase (TBK)1, IkappaB kinase-epsilon (IKK-ε) and nuclear factor-kappaB (NF-κB) were analyzed with or without ANG treatment in tumor necrosis factor-alpha (TNF-α)- or lipopolysaccharide (LPS)-induced inflammatory HCFs by real-time polymerase chain reaction (PCR), Western blotting and immunocytochemistry. Inflammatory cytokine profiles with or without ANG were evaluated through immunodot blot analysis in inflammatory HCFs. Corneal neovascularization and opacity in a rat model of corneal alkali burn were evaluated after application of ANG eye drops. Results ANG decreased the mRNA levels of IL-1β, IL-6, IL-8, TNF-α receptor (TNFR)1, 2, TLR4, MYD88, and complement components except for C1r and C1s and elevated the mRNA expression of IL-4 and IL-10. Increased signal intensity of IL-6, IL-8 and monocyte chemotactic protein (MCP)-1 and MCP-2 induced by TNF-α or LPS was weakened by ANG treatment. ANG reduced the protein levels of IKK-ε by either TNF-α and LPS, and decreased TBK1 production induced by TNF-α, but not induced by LPS. The expression of NF-κB in the nuclei was decreased after ANG treatment. ANG application lowered corneal neovascularization and opacity in rats compared to controls. Conclusion These results demonstrate that ANG reduces the inflammatory response induced by TNF-α or LPS in HCFs through common suppression of IKK-ε-mediated activation of NF-κB. This may support the targeting of immune-mediated corneal inflammation by using ANG.